TINJAUAN TERHADAP PELAKSANAAN CSR PT TIRTA INVESTAMA AIRMADIDI DI DESA TUMALUNTUNG KEC KAUDITAN PASCA BERLAKUNYA UU NO 40 TAHUN 2007 TENTANG PERSEROAN TERBATAS DEMI TERWUJUDNYA PEMBANGUNAN BERKELANJUTAN - Kaunang, Shandy; Diana Putong; Feibe Engeline Pijoh (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2022)
Corporate Social Responsibility is set in article 74 of Law No. 40 of 2007 on Limited Liability Company. Corporates have to do corporate social and environmental responsibility. In sustainable development context, there are three values to be applied in corporates CSR, such as economic, social, and environmental. In the implementation of CSR, corporate must set plan and allocate funds from the revenues of the company worthily. Based on the background, the problem formulation is how is the implementation of PT. Tirta Investama Airmadidi CSR by way of Organic farmer and Biogas based on Law No. 40 of 2007 on Limited Liability Company? The purpose of Organic farmer and Biogas this study are to investigate the implementation of PT. Tirta Investama Airmadidi CSR by way of based on Law No. 40 of 2007 on Limited Liability Company. In the implementation, PT. Tirta Investama Airmadidi CSR by way of Organic farmer and Biogas experience some technical problems. Organic farmer and Biogas don’t provide a significant change to the community’s economic, and the result, it doesn’t have impact on community’s prosperity. In addition, the conducted Organic farmer and Biogas doesn’t fulfill the fit and proper values.